2021
DOI: 10.3390/ijms221910230
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Discovery and Function of Antimicrobial Molecules in Platelets

Abstract: The conventional function described for platelets is maintaining vascular integrity. Nevertheless, increasing evidence reveals that platelets can additionally play a crucial role in responding against microorganisms. Activated platelets release molecules with antimicrobial activity. This ability was first demonstrated in rabbit serum after coagulation and later in rabbit platelets stimulated with thrombin. Currently, multiple discoveries have allowed the identification and characterization of PMPs (platelet mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 172 publications
(189 reference statements)
0
18
0
2
Order By: Relevance
“…Platelets are the smallest circulating cells primarily involved in hemostasis but have gained interest due to their participation in divergent functions, including the immune response. In innate host defense, platelets produce antimicrobial and chemoattractant mediators [ 6 , 21 ]. Nevertheless, the presence of azurocidin protein in platelets and megakaryoblasts had not been fully characterized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Platelets are the smallest circulating cells primarily involved in hemostasis but have gained interest due to their participation in divergent functions, including the immune response. In innate host defense, platelets produce antimicrobial and chemoattractant mediators [ 6 , 21 ]. Nevertheless, the presence of azurocidin protein in platelets and megakaryoblasts had not been fully characterized.…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently confirmed the expression of azurocidin protein, within the α-granule, of both platelets and Meg-01 cells, in the latter also in an extra-granular manner. In addition to azurocidin, it is now known that α-granules contain a variety of molecules with microbicidal activity, such as Basic Platelet Protein (PBP), CXCL4, CCL5, and HNP-1 (defensin-α1) [ 6 ]. Recently, it has been shown that megakaryocytes contain and transfer defensin-α1 to nascent platelets, although they can also acquire it from plasma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides their crucial role in haemostasis, platelets are progressively considered as immune-competent cells participating in inflammation and immunity. Platelets were shown to directly contribute to anti-viral and anti-bacterial immunity by release of microbicidal factors, pathogen engulfment or aggregate formation [9][10][11]. In particular, by interaction with lymphocytes platelets are capable of affecting their immunological functions.…”
Section: Introductionmentioning
confidence: 99%